BUSINESS SCALE, BUSINESS AGE, AND KNOWLEDGE OF ACCOUNTING ON INTEREST IN USING ACCOUNTING INFORMATION - Andi Resky Rahim; Sumarlin Sumarlin (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract, This study aims to examine the factors that influence the use of accounting information by using variables of business scale, age of business, and accounting knowledge. The type of research used is quantitative research. Data collection techniques using questionnaires. The regression model used in this study is a multiple linear regression model with the help of SPSS. The sampling method for the study used the Random Sampling method (random) which obtained as many as 95 MSME owners/managers in Somba Opu District, Gowa Regency. The results showed that the variables of business scale, business age and accounting knowledge had a positive and significant effect on the use of accounting information in MSME’s Somba Opu District, Gowa Regency. The implication of this research is that MSME actors are expected to better understand and use accounting information, especially for financial information, to pay more attention because the existence of financial reports for MSMEs can help MSMEs in applying for credit to banks if they need capital. For the government and related agencies, they must help SMEs to use accounting information more, one of which is by holding trainings related to accounting information. In addition, further research with the same theme is expected to add other variables that can affect the use of accounting information, so that the results of the study can explain the contribution of all these variables to the use of accounting information. Abstrak, Penelitian ini bertujuan untuk menguji faktor-faktor yang mempengaruhi penggunaan informasi akuntansi dengan menggunakan variabel skala usaha, umur usaha, dan pengetahuan akuntansi. Jenis penelitian yang digunakan adalah penelitian kuantitatif. Teknik pengumpulan data menggunakan kuesioner. Model regresi yang digunakan dalam penelitian ini adalah model regresi linier berganda dengan bantuan SPSS. Metode pengambilan sampel penelitian menggunakan metode Random Sampling (acak) yang diperoleh sebanyak 95 orang pemilik/pengelola UMKM di Kecamatan Somba Opu Kabupaten Gowa. Hasil penelitian menunjukkan bahwa variabel skala usaha, umur usaha dan pengetahuan akuntansi berpengaruh positif dan signifikan terhadap penggunaan informasi akuntansi pada UMKM Kecamatan Somba Opu Kabupaten Gowa. Implikasi dari penelitian ini adalah para pelaku UMKM diharapkan lebih memahami dan menggunakan informasi akuntansi khususnya untuk informasi keuangan agar lebih diperhatikan karena dengan adanya laporan keuangan UMKM dapat membantu UMKM dalam mengajukan kredit ke bank jika membutuhkan modal. Bagi pemerintah dan instansi terkait harus membantu UKM agar lebih banyak menggunakan informasi akuntansi, salah satunya dengan mengadakan pelatihan-pelatihan terkait informasi akuntansi. Selain itu, penelitian selanjutnya dengan tema yang sama diharapkan menambahkan variabel lain yang dapat mempengaruhi penggunaan informasi akuntansi, sehingga hasil penelitian dapat menjelaskan kontribusi semua variabel tersebut terhadap penggunaan informasi akuntansi.